2019
DOI: 10.1021/acsaem.9b01207
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Optimized Thermoelectric Performance in Bi0.48Sb1.52Te3 by Hot Deformation and Cu Doping

Abstract: In recent decades, bismuth telluride (Bi2Te3) has been in widespread use for normal-temperature thermoelectric cooling. However, commercial zone-melted bismuth telluride faces the big challenge of dramatically decreased thermoelectric properties at higher temperature, which limits its usage at intermediate temperature. In this contribution, the thermoelectric performance of p-type bismuth telluride is enhanced via a synergistic optimization by hot deformation and copper doping. Hot deformation treatment boosts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 47 publications
0
27
1
Order By: Relevance
“…[53][54][55][56][57][58] Despite many studies having found equations given by λ 2 ¼ constant (V ) À2/3 for different alloy systems, [59][60][61][62] the effects of lateral solute segregation on the wavelengths of instabilities along the sides of primary dendritic stems for Bi-based alloys are still not well understood. Herein, a single power law in which the exponent À1.1 characterizes the experimental evolution of λ 2 as a function of V L for all Bi- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) wt% Sb alloys is proposed. Figure 10 shows Vickers microhardness (HV) for the analyzed Bi-Sb alloys as a function of Sb concentration along the length of DS castings, highlighting the solidification microstructure morphologies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[53][54][55][56][57][58] Despite many studies having found equations given by λ 2 ¼ constant (V ) À2/3 for different alloy systems, [59][60][61][62] the effects of lateral solute segregation on the wavelengths of instabilities along the sides of primary dendritic stems for Bi-based alloys are still not well understood. Herein, a single power law in which the exponent À1.1 characterizes the experimental evolution of λ 2 as a function of V L for all Bi- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) wt% Sb alloys is proposed. Figure 10 shows Vickers microhardness (HV) for the analyzed Bi-Sb alloys as a function of Sb concentration along the length of DS castings, highlighting the solidification microstructure morphologies.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, Bi-based alloys are highlighted as potential Pb-free alloys for the replacement of the conventional Sn-Pb solder TIMs used in electronic assemblies. [12] As a matter of fact, Bi-based alloys are also suggested for various applications as thermoelectric materials, [13][14][15] optical and electro-optical devices, [16] hall sensors, [17] and lubricant materials. [18] However, the great challenge in developing new Bi alloys is the enhancement of a specific property without compromising other important physical properties, as stated by Septimio et al [19] From this perspective, controlling the microstructure through solidification thermal parameters is of critical importance because it plays an important role on the resulting properties of metallic alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Recently, hot pressing has become a relatively mature technique for the preparation of thermoelectric nanocomposites. 38,[48][49][50] Because of the thermoplasticity of the polymer matrix, most dense organic-inorganic composites can be fabricated via a simple homemade hot pressing device. J. Kim et al 51 prepared n-type carbon bucky paper with carbon nanotubes and a PVDF composite via hot pressing at 60 1C in 6 MPa for 3 min.…”
Section: Hot Pressing or Spark Plasma Sinteringmentioning
confidence: 99%
“…44 Obviously, both LPS and HD processes contribute to texture modulation and result in better electronic properties as well as mechanical properties in SnSe-based materials. Nevertheless, the HD procedure is somewhat complicated and energy-consuming with poor repeatability, [44][45][46][47][48] while the LPS process may induce a higher thermal conductivity. 43,[49][50][51] Recently, the liquid-phase hot deformation (LPHD) technique was proposed in n-type Bi 2 (Te,Se) 3 alloys.…”
Section: Introductionmentioning
confidence: 99%